Pulsatile-flow mechanical circulatory support (MCS) as a bridge to transplantation or recovery. Single-centre experience with the POLCAS system in 2014 - Kuśmierczyk, Mariusz; Kuć, Mateusz; Szymański, Jarosław; Juraszek, Andrzej; Kołsut, Piotr; Kuśmierski, Krzysztof; Zieliński, Tomasz; Sobieszczańska-Małek, Małgorzata; Sitkowska-Rysiak, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Mechanical circulatory support (MCS) is a recognised method of treatment for patients with end-stage chronic or acute heart failure. The POLCAS pulsatile-flow system has been used in our institution for 15 years. Currently, it is being widely replaced by continuous-flow mechanical circulatory support equipment of the second and third generations (HeartMateII, HeartWare). The MCS presented in this study is associated with a significant risk of complications and its use is increasingly considered controversial. The aim of the study was an evaluation of the results of treatment utilising the POLCAS MCS system at our institution in 2014. Material and methods : The POLCAS system was implanted in 12 patients aged 16-63 years (42 ± 17 years) during a period of 12 months (from January to December, 2014). Full-blown cardiogenic shock was observed in all patients before MCS implantation. Four of the analysed patients (33%) required prior circulatory support with other devices: IABP (n = 2) or ECMO (n = 2). Episodes of cardiac arrest were reported in three patients; three other patients experienced serious arrhythmias, which accelerated the decision to implant MCS. The presented data was retrospectively obtained from the CliniNET system of the Institute of Cardiology. OpenOffice Calc spreadsheet was used for data analysis. Results : Average MCS time was 41 days ± 25 (from 15 to 91 days). Survival until transplantation or explantation was 91.67%. The most frequent complications following the therapy were: cardiac tamponade or bleeding requiring an intervention – 25% (n = 3), renal failure requiring dialysis – 25% (n = 3), ischaemic stroke associated with the MCS – 16.6% (n = 2), bacteraemia – 16.6% (n = 2), and wound infection – 8% (n = 1). No malfunctions of the MCS system were reported. Early survival in patients who completed the MCS therapy, defined as discharge, amounted to 63.6% (n = 7). Conclusions : The POLCAS heart assist system is an effective method of treatment as a bridge to transplantation or recovery in patients with end-stage heart failure. Early survival after the treatment remains at a satisfactory level. The main problem is the large number of complications related to the therapy.